Housing with care: queer geographies and the right to the city of LGBTQ+ urban communities. The Co-housing Queerinale/Agapanto project (Rome) - Marocco, Anna (Scienze del Territorio, 2023)
Feminist geography and epistemologies, since their beginnings, have encouraged us to start again from our bodies as situated geographies, from their experiences and embodied knowledge, to expose the power relations produced by the capitalist heteropatriarchal order and imprinted in the surrounding spaces. The body represents both the privileged dimension from which dynamics of violence, oppression and exploitation are experienced, and the place where new counter-hegemonic practices and forms of embodied knowledge may be produced. Starting with the notion of Wasteocene (2021) – an era marked by the continuous production of cast-off people, communities and places – by the landscape historian Marco Armiero, I will cross some toxic narratives typical of our society, all dear to neoliberal carelessness that inexorably produce waste and marginality. Opposed to these toxic discursive relations and constructions are the commoning practices, as those collective practices that simultaneously generate common goods and communities oriented towards care and inclusion. Along this path, I will present the Queerinale project promoted by the Agapanto Association for the conversion of a disused public building into a collaborative housing for LGBTQ+ elderly in the city of Rome, to re-signify our housing models and suggest new orientations for public policies.